1996
DOI: 10.1083/jcb.135.6.1815
|View full text |Cite
|
Sign up to set email alerts
|

Centractin (ARP1) associates with spectrin revealing a potential mechanism to link dynactin to intracellular organelles.

Abstract: Abstract. Centractin (Arpl), an actin-related protein, is a component of the dynactin complex. To investigate potential functions of the protein, we used transient transfections to overexpress centractin in mammalian cells. We observed that the overexpressed polypeptide formed filamentous structures that were significantly longer and more variable in length than those observed in the native dynactin complex. The centractin filaments were distinct from conventional actin in subunit composition and pharmacology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
187
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(191 citation statements)
references
References 87 publications
3
187
0
1
Order By: Relevance
“…On the other hand, it is well known that dynactin interacts with and activates cytoplasmic dynein (33). Further, it has been shown that dynactin may recruit dynein to cargo in membrane vesicles directly (34) or indirectly via cytoskeletal proteins such as spectrin (35)(36)(37). Hence, in our future work, we will test the prediction that dynactin and spectrin may mediate the interaction between ClC-2 and dynein.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, it is well known that dynactin interacts with and activates cytoplasmic dynein (33). Further, it has been shown that dynactin may recruit dynein to cargo in membrane vesicles directly (34) or indirectly via cytoskeletal proteins such as spectrin (35)(36)(37). Hence, in our future work, we will test the prediction that dynactin and spectrin may mediate the interaction between ClC-2 and dynein.…”
Section: Discussionmentioning
confidence: 90%
“…The only other known adapter that links a motor to its cargo is dynactin, a 20S multisubunit complex that interacts with cytoplasmic dynein (16)(17)(18). Dynactin is important for docking dynein onto various types of cargo, including the Golgi apparatus (19), lysosomes (20), and kinetochores (21). Similarly, it will be interesting to establish whether She3p serves as a general Myo4p adapter for various cargo besides Ash1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Dynactin might interact directly with components of the lipid bilayer (13), but extraction studies suggest that dynactin is more peripherally associated with organelle membranes via protein-protein interactions (1). Based on observations of cells overexpressing the Arp1 subunit of dynactin, we previously proposed that the association of dynactin with vesicles is mediated by an interaction between Arp1 and an organelle-associated spectrin (11,14).Conventional spectrin associates with the cytoplasmic face of the plasma membrane, forming orthogonal arrays that are connected by 37-nm actin filaments and that are attached to the membrane by peripheral and integral membrane proteins (15, 16). A noncortical role for spectrin has also been proposed.…”
mentioning
confidence: 99%
“…Dynactin might interact directly with components of the lipid bilayer (13), but extraction studies suggest that dynactin is more peripherally associated with organelle membranes via protein-protein interactions (1). Based on observations of cells overexpressing the Arp1 subunit of dynactin, we previously proposed that the association of dynactin with vesicles is mediated by an interaction between Arp1 and an organelle-associated spectrin (11,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation